BANKING INTERMEDIATION AND ECONOMIC GROWTH IN THE CONGO : CORRELATION AND CAUSALITY - Hortense Elenga (Galaxy International Interdisciplinary Research Journal, 2022)
This article on the linear relationship between banking intermediation and economic growth consisted in determining the correlative and causal relationship between these two phenomena in Congo for the period from 1973 to 2015. Estimates using the Johansen cointegration test and the Vector Error Correction Model (VCEM) on seven variables (GROWTH, PRIV, GOV, OPEN, INFL, TBSS, and IPRIV) revealed a negative and significant correlative relationship between these two phenomena in the case of Congo. This result corroborates that of the post-Keynesians. In this case, the causal relationship goes from economic growth to bank intermediation.